2021
DOI: 10.15190/d.2021.5
|View full text |Cite
|
Sign up to set email alerts
|

High mortality co-infections of COVID-19 patients: mucormycosis and other fungal infections

Abstract: Severe COVID-19 disease is associated with an increase in pro-inflammatory markers, such as IL-1, IL-6, and tumor necrosis alpha, less CD4 interferon-gamma expression, and fewer CD4 and CD8 cells, which increase the susceptibility to bacterial and fungal infections. One such opportunistic fungal infection is mucormycosis. Initially, it was debated whether a person taking immunosuppressants, such as corticosteroids, and monoclonal antibodies will be at higher risk for COVID-19 or whether the immunosuppresive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
122
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 39 publications
3
122
0
5
Order By: Relevance
“…As summarized in Tables 1 and 2 , most patients had severe COVID-19 pneumonia requiring intensive care, intubation and ventilation. In addition, most patients had underlying diabetes mellitus and received steroids [ 28 , 64 , 65 ]. The presence of diabetes mellitus is a major predisposing factor for mucormycosis as described in a meta-analysis among 600 (70%) of 851 patients with rhino-orbital–cerebral mucormycosis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As summarized in Tables 1 and 2 , most patients had severe COVID-19 pneumonia requiring intensive care, intubation and ventilation. In addition, most patients had underlying diabetes mellitus and received steroids [ 28 , 64 , 65 ]. The presence of diabetes mellitus is a major predisposing factor for mucormycosis as described in a meta-analysis among 600 (70%) of 851 patients with rhino-orbital–cerebral mucormycosis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a person taking immunosuppressants, such as corticosteroids and monoclonal antibodies, may experience severe lymphocytopenia. Because lymphocytes play an important role in the immune defense function against infection, patients with COVID-19 are highly susceptible to bacterial and fungal secondary infections causing a high mortality rate in patients with COVID-19 (Bhatt et al 2021 ). About 3.6–13% of patients with COVID-19 developed a secondary bacterial or fungal infection and the mortality rate among these patients was about 33.3–56.7% (Khurana et al 2021 ; Vijay et al 2021 ).…”
Section: Potential Therapeutic Effects Of Boswellic Acids and B Serrata Extract Against Covid-19-induced Secondary Micmentioning
confidence: 99%
“…New coronavirus disease (COVID-19) continues to exhibit remarkable repercussions worldwide along with its atypical manifestations. Novel reports of SARS-CoV-2 infection underline the risk of opportunistic fungi infections, namely the pulmonary aspergillosis and mucormycosis, that accompany viral symptoms, leading to death by invading multi-organ systems [ 1 ]. Experience from SARS patients showed that incidence of fungal co-infection was 14.8–27%, and it was higher in severely ill SARS patients reaching up to 33% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%